Bryophytes of mine dumps in Chervonograd industrial coal mining region (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
As a result of bryoflora inventory of mine dumps in Chervonograd industrial coal mining region 38 species of mosses belonging to two orders of Marchantiophyta (3 families, 3 genera, 3 species) and Bryophyta (15 families, 24 genera, 35 species) were found. For the investigated territory 7 rare species of mosses have been determined. Firstly, Campylopus introflexus and Pohlia sphagnicola have been discovered for bryoflora of Ukraine on the dumps of mine “Nadija” (Sosnivka of Lviv region). The results of complex analysis of devastated territories bryoflora and characteristics of its structure have been provided.
Keywords: bryophytes, rare species, mine dumps, reproductive plasticity, ecomorphs, life form, life strategy.